2000
DOI: 10.1063/1.373861
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser annealing for high-efficiency thin film electroluminescent devices

Abstract: Articles you may be interested inInfluence of a two-dimensional SiO 2 nanorod structure on the extraction efficiency of ZnS:Mn thin-film electroluminescent devices Improved brightness, efficiency, and stability of sputter deposited alternating current thin film electroluminescent ZnS:Mn by codoping with potassium chloride

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Hence, we inferred that laser annealing can produce the required activation of the thin film phosphors while maintaining a suitable interface state distribution. 29 To conclude, the results of our studies are further evidence that it is important to control the interfacial structure during annealing in order to obtain high-efficiency TFEL devices.…”
Section: Performance Limitation Of Tfel Devices At High Thermal Anmentioning
confidence: 62%
See 1 more Smart Citation
“…Hence, we inferred that laser annealing can produce the required activation of the thin film phosphors while maintaining a suitable interface state distribution. 29 To conclude, the results of our studies are further evidence that it is important to control the interfacial structure during annealing in order to obtain high-efficiency TFEL devices.…”
Section: Performance Limitation Of Tfel Devices At High Thermal Anmentioning
confidence: 62%
“…Very recently, we reported laser processed TFEL devices exhibiting better display performance than equivalent devices thermally annealed at 450°C, as demonstrated by the maintenance of a sharp luminance against voltage characteristic with no drop in threshold voltage and a fourfold increase in brightness. 29 Interestingly, the lattice misfit values measured from similarly laser annealed NTU259 structures are smaller than 1.40, 29 which is lower than the values measured from thermally annealed NTU259 structures at 500°C ͑Table II͒. Hence, we inferred that laser annealing can produce the required activation of the thin film phosphors while maintaining a suitable interface state distribution.…”
Section: Performance Limitation Of Tfel Devices At High Thermal Anmentioning
confidence: 64%
“…We consider that the greatest benefit of laser annealing lies with the fact that it performs highly localized heat treatment [8]. As mentioned earlier, this permits the usage of temperature sensitive substrates, which would allow the application of the mature display technology of TFEL for producing flexible displays.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has shown that transparent ITO and Y 2 O 3 can be deposited onto polymeric materials using HiTUS, without damaging the substrate [5,6]. Additionally, due to the localized heating of the laser used throughout this work, it has been shown that the annealing process can be applied to thin films deposited onto temperature-sensitive substrate materials [7]. Hence the work here presents the first step to realizing high-luminance, fully transparent EL devices on flexible substrates.…”
Section: Introductionmentioning
confidence: 93%